Auditoría de gestión al departamento de recursos humanos de la empresa Novacero s.a. ubicada en la ciudad de Latacunga provincia de Cotopaxi, por el período comprendido del 01 de enero al 31 de diciembre del 2014 - Espinosa Moreno, Erika Gissela (2016)
This research work was aimed at implementing a Management Audit to the Human Resources Department in NOVACERO Enterprise SA during the period 2014, in order to assess the level of compliance goals with efficiency and affectivity in the use of the resources to develop the activities, due to the relevant weakness found in the department because of the operative overloading; it causes delay with the planned activities execution. To develop this Management Audit, real and objective information was used directly provided by the staff company, through the use of investigative techniques such as surveys to the staff and an interview with the Department Head, therefore it was determined the actual situation in the area and it was based on the results of the implementation of a management so that, an audit was deemed necessary….